Me not a good kisser, that’s like Mother Theresa, not a good mother. An Analysis of the Hyperbolic like Comparison Construction: - Rosca, Andreea (International Journal of English Studies, 2024)
Given the scarcity of research on hyperbole and simile in Cognitive Linguistics, it is important to explore these figures of speech, whose interaction has only been tangentially addressed in this field. Thus, the main aim of the study is to provide a detailed description of hyperbolic like comparison constructions by examining the structural and conceptual diversity of the source and target domains, as well as the characteristics of the third component of hyperbolic similes, namely the elaboration. With this objective in mind, we carried out an analysis of 120 examples of hyperbolic similes retrieved from the comedy sitcom Friends (1994-2004). Our findings show that the source domains of hyperbolic like comparison constructions are both structurally and conceptually more complex than the target domains.